Association of gait and balance disorders with age-related white matter changes: the LADIS Study - Bäzner, Hansjörg; Blahak, Christian; Poggesi, A.; Pantoni, L.; Inzitari, D.; Chabriat, H.; Erkinjuntti, T.; Fazekas, F.; Ferro, J. M.; Langhorne, P.; O’Brien, J.; Scheltens, P.; et al. (Neurology, 2008)
Objective: In the Leukoaraiosis and Disability (LADIS) Study, 11 European centers are evaluating the role of age-related white matter changes (ARWMC) as an independent determinant of the transition to disability in the elderly (65 to 84 years). We aimed at determining the influence of ARWMC on different objective measures of gait and balance. - Methods: Six hundred thirty-nine nondisabled individuals were prospectively enrolled and are being followed-up for 3 years. Subjects are graded in three standardized categories of ARWMC (mild, moderate, and severe) according to central MRI reading. Quantitative tests of gait and balance include the Short Physical Performance Battery (SPPB; range: 0 [poor] to 12 [normal]), a timed 8-m walk, and a timed single leg stance test. - Results: In cross-sectional analysis, deficiencies in gait and balance performance were correlated with the severity of ARWMC (SPPB: 10.2 ± 2.1 in the mild, 9.9 ± 2.0 in the moderate, 8.9 ± 2.6 in the severe group; p < 0.001). Walking speed correlated with the severity of ARWMC (1.24 ± 0.28 m/second in the mild, 1.18 ± 0.32 m/second in the moderate, and 1.09 ± 0.31 m/second in the severe group; p < 0.001). Balance was best in individuals with mild ARWMC (single leg stance time: 18.9 ± 10.8 seconds) compared with moderate and severe ARWMC (16.4 ± 10.8 and 13.6 ± 11.2 seconds) (p < 0.001). Physically inactive individuals had a higher risk of a pathologic SPPB score (moderate vs mild ARWMC: odds ratio 1.60, 95% CI 1.02 to 2.52; severe vs mild ARWMC: odds ratio 1.75, 95% CI 1.09 to 2.80). - Conclusions: Our findings support a strong association between the severity of age-related white matter changes and the severity of gait and motor compromise. Physical activity might have the potential to reduce the risk of limitations in mobility.
Gesehen am 26.03.2021